Neurotransmitter and Related Metabolic Profiling in the Nucleus Accumbens of Chronic Unpredictable Mild Stress-Induced Anhedonia-Like Rats - Li, Yan; Chen, Zhi; Zhao, Jianting; Yu, Heming; Chen, Xiangyu; He, Yong; Tian, Yu; Wang, Yue; Chen, Chong; Cheng, Ke; Xie, Peng (Frontiers in Behavioral Neuroscience, 2022)
Major depressive disorder (MDD) is a severe mental disorder that affects many people. The neurotransmitter deficiency hypothesis has been the crux of much research into treatment for depression. Here, we investigated changes in neurotransmitter and related metabolite in the GABAergic, serotonergic and catecholaminergic pathways in the nucleus accumbens (NAc) of a rat model of chronic unpredictable mild stress (CUMS) induced depression. Sprague-Dawley rats were used for the CUMS model. Depressive behaviors were evaluated with behavioral tests. Liquid chromatography-tandem mass spectrometry was employed to detect targeted neurotransmitter and related metabolite in the NAc. Western blot was used to assess the expression of key enzymes and receptors. Rats exposed to CUMS were divided into stress-susceptible and stress-resilient groups according to sucrose preference. In the GABAergic pathway in the NAc, glutamate was increased both in susceptible and resilient rats while glutamine was only increased in resilient rats. In the serotoninergic pathway, 5-HT in stress-susceptible rats was increased, and the 5-hydroxytryptophan was also significantly increased in susceptible rats. In the catecholaminergic pathway, L-phenylalanine and tyramine also showed significant changes. The expression of the key enzyme monoamine oxidase A was significantly decreased in susceptible rats, while it was increased in resilient rats; The glutamate receptor family showed a tendency similar to 5-HT. Thus, Serotoninergic and GABAergic metabolite disorders may be important factors contributing to in susceptibility or resilience to stress. These changes may serve as new insight for understanding the development of depression.